UPAYA PENCEGAHAN DAN PENANGGULANGAN PERMASALAHAN STUNTING DI DESA CILAMAJANG, KOTA TASIKMALAYA - Ilmaa, Miftahul; Amalia, Nurul Firda; Setiadi, Pidi Mohamad Setiadi (BESIRU : Jurnal Pengabdian Masyarakat, 2024)
ABSTRACKHealth is a gift that should be grateful for and maintained, nutrition is part of health. Balanced nutrition can support the creation of a healthy and fit body. However, quite a few nutritional problems arise, one of which is the nutritional problem of stunting. Indonesia is being shocked by the nutritional problem of stunting. Problems that cause stunting in the subdistrict where we serve include babies being born stunted. This lack of nutritional intake can occur when the baby is still in the womb because the mother does not meet nutritional needs during pregnancy and lacks nutritional intake when the child is full of breast milk. Research carried out in Cilamajang Village, Tasikmalaya City in August 2023. This research method aims to find out and studying toddlers who have nutritional problems in Cilamajang Village, which is a phenomenological research study with a qualitative descriptive approach. The total number of community service activities carried out is approximately one month, which includes planning, implementation and evaluation activities. In the first step, the Community Service team identified village potential that could be used to solve the stunting problem in Cilamajang.